Tumor-Associated Macrophages in Glioma: Friend or Foe?. (8th May 2013) - Kennedy, Benjamin C.; Showers, Christopher R.; Anderson, David E.; Anderson, Lisa; Canoll, Peter; Bruce, Jeffrey N.; Anderson, Richard C. E.
Abstract : Tumor-associated macrophages (TAMs) contribute substantially to the tumor mass of gliomas and have been shown to play a major role in the creation of a tumor microenvironment that promotes tumor progression. Shortcomings of attempts at antiglioma immunotherapy may result from a failure to adequately address these effects. Emerging evidence supports an independent categorization of glioma TAMs as alternatively activated M2-type macrophages, in contrast to classically activated proinflammatory M1-type macrophages. These M2-type macrophages exert glioma-supportive effects through reduced anti-tumor functions, increased expression of immunosuppressive mediators, and nonimmune tumor promotion through expression of trophic and invasion-facilitating substances. Much of our work has demonstrated these features of glioma TAMs, and together with the supporting literature will be reviewed here. Additionally, the dynamics of glioma cell-TAM interaction over the course of tumor development remain poorly understood; our efforts to elucidate glioma cell-TAM dynamics are summarized. Finally, the molecular pathways which underlie M2-type TAM polarization and gene expression similarly require further investigation, and may present the most potent targets for immunotherapeutic intervention. Highlighting recent evidence implicating the transcription factor STAT3 in immunosuppressive tumorigenic glioma TAMs, we advocate for gene array-based approaches to identify yet unappreciated expression regulators and effector molecules important to M2-type glioma TAMs polarization and function within the glioma tumor microenvironment.